Worktime control: theoretical conceptualization, current empirical knowledge, and research agenda - Debby GJ Beckers; Michiel AJ Kompier; Göran Kecklund; Mikko Härmä (Nordic Association of Occupational Safety and Health (NOROSH), 2012)
Working hours play a crucial role in the life, health, and well-being of workers. Concerning irregular working hours, the recent Fifth European Working Conditions Survey (1) shows that night work is carried out by 19% and shift work by 17% of all workers in Europe. More than half of the total workforce works at least one day during the weekend and 21% works "on call". The health effects of night and shift work have been a popular and important area of research within Scandinavian Journal of Work, Environment & Health (eg, 2-4), including new and interesting data and a consensus statement on shift work and breast cancer (5) published in this issue (5-8). As working times are becoming increasingly irregular and flexible, their associations with work-life balance, work satisfaction, mental health, and productivity are of growing interest. Regarding worktime flexibility, the literature distinguishes between company-based and employee-oriented flexibility (9-13). The former refers to "the need of employers to extend, modify, or reduce work hours according to client or production needs" (10, p503). Shift work and mandatory overtime are well-known examples. Employee-oriented worktime flexibility refers to autonomy regarding working times with the aim of meeting employee needs (14). A similar construct is worktime control (WTC): "an employee's perception of his/her possibilities to control the duration, position, and distribution of his/her working times" (10, p503). WTC refers to self-determination of worktime aspects such as starting and ending times of the work day, breaks, days off, vacations (9), and control over whether, when and how much to work overtime (15). The distinction between company-based and employee-oriented worktime flexibility is helpful but one must bear in mind that a clear distinction is not always possible: although scholars tend to present WTC as a form of employee-oriented flexibility, it may also be implemented to advance organizational needs, such as higher work motivation and productivity and lower absenteeism and turnover of valued employees (16). Applications of worktime flexibility are by no means new phenomena. Company-based shift work has been a health issue in Europe since the end of the 19th century (17). WTC was pioneered at a German company in 1967, in the form of "gliding time" (cf. flextime). This early experiment resulted in favorable organizational outcomes and, from 1970 onwards, flextime spread in West-European countries (18). Yet, until the late 20th century, patterns of work schedules remained quite uniform, and work hours were still mainly determined by the employer with limited freedom on the part of employees (11, 18). During the 1990s, major trends towards enhanced employee-oriented WTC emerged. This was a reaction to the louder call for "healthy work" and the rising labor participation of women and associated challenges regarding successfully combining work and family (11). In the 21st century, the trend towards more flexible worktime practices continues. Many organizations aim at flexible worktime arrangements that combine company-based and employee-oriented flexibility. An interesting example of a relatively new and intense flexible worktime intervention is self-scheduling, mostly applied in shift work settings. The employer defines the number of workers needed for several specific time units (eg, for each hour of each working day over a specific time period) and employees can then choose their own working hours by signing up for specific time units, thereby taking into account their personal preferences, worktime regulations, and the minimum number of work hours they have to work according to their contract. Another flexible worktime practice that has gained popularity is "boundaryless work" - also known as "trust hours" (13) - which basically combines intensive employee WTC and spatial flexibility among white-collar workers. As a consequence, the traditional work day characterized by 8 hours of work, 8 hours of free time, and 8 hours of sleep, might be replaced by a different time structure in which work and private life are much more integrated. A well-known symptom of such integration is that many contemporary workers stay in contact with work during evenings, days off, weekends, and vacations, which is in some cases even expected by their employers. Not only individual employers and employees are increasingly engaged in promoting employee WTC, also several European countries (eg, UK and Scandinavian countries) stimulate WTC by introducing national legislation that enables employees to request employee-oriented flexible working times (12). In The Netherlands, such legislation is currently proposed to be included in the Dutch Work Directive. All in all, these efforts at multiple societal levels have led to a considerable prevalence of employee WTC in many European countries. A recent international survey among 27 000 European companies showed that 57% of all European companies applied some type of flextime arrangement. This marks a vast increase over the 48% in 2004 (19). WTC is most prominent in North-European companies: 60-80% of all companies within Finland, Denmark, Sweden, UK, and Germany indulge flextime. It is less pronounced in East Europe [circa 33%; (19)]. Against this background, the Scandinavian Journal of Work, Environment & Health decided to publish a thematic issue on WTC. The aim is to provide an overview of current scientific knowledge about the effects of WTC on employee- and organizational outcomes and advance knowledge on the effects of self-scheduling. In this editorial, we briefly summarize relevant theoretical and empirical insights regarding WTC. We also introduce a research agenda. Theoretical insights and empirical findings on the effects of worktime control Theoretical groundings for the assumed benefits of increased WTC for both employees and organizations stem from several motivational and occupational health theories. From the perspective of Effort-Recovery Theory (20), WTC can be assumed to promote a favorable balance between effort and recovery as it stimulates internal recovery opportunities, by means of control over breaks, and external recovery, as employees can adjust their working and recuperation time to their current need for recovery. Three other key occupational health theories [ie, Self-Determination Theory (21), the Job Characteristics Model (22), and the Job Demands-Control Model (23)] suggest that WTC - as a subdimension of general autonomy - may stimulate worker motivation, health, and performance, and may prevent stress, absenteeism, and turnover. WTC can influence these outcomes by means of at least two processes: (i) through the actual utilization of WTC and associated change in working times and related work characteristics; and (ii) the mere opportunity to self-determine working hours may stimulate favorable outcomes, irrespective of an actual change in working times (this could be called a "psychological process"). Finally, based on theories of work-home interaction (24), WTC can be expected to advance a better work-non-work balance (and thus prevent stress), as WTC enables the adjustment of working time to meet obligations, needs, and activities in private life. Following such theoretical insights, Baltes and colleagues (16) decided to empirically substantiate whether flextime interventions indeed stimulate favorable organizational outcomes. In a meta-analysis of 27 intervention studies, these authors concluded that flextime (ie, employee control over starting and ending times of the work day) can have positive effects on organizational outcomes (ie, productivity, job satisfaction, absenteeism, and satisfaction with work schedule). However, differences in effect sizes were found, indicating that flextime is more likely to impact attendance (absenteeism) than directly impact worker effectiveness (productivity). In the first contribution of this thematic issue, Nijp and colleagues (15) build upon this meta-analysis. They systematically review the scientific literature - published between 1995 and 2011 - on the association between the broad concept of WTC on the one hand (general as well as several specific aspects of WTC, eg, flextime and leave control) and employee- and organizational outcomes on the other.